Land grabbing, Global Food Security and Transnational Agribusiness: Instrumentalism or National Law Ideationalism (Law Research Review Quarterly, 2015)
Large-scale, long-term land tenure operations by transnational business entities that run food crop cultivation businesses for export. The phenomenon of land grabbing for global food security in the 21st century has emerged since 2008-2009, along with skyrocketing global food prices. It cannot be denied that high population growth is positively correlated with consumption levels.